0214 Cancer mortality in the British Rubber industry - a 45 year follow-up. (23rd June 2014) - McElvenny, Damien; Agius, Raymond; Cherrie, John; de Vocht, Frank
Abstract : Objectives: Working in the rubber and rubber product manufacturing industry has been classified by the International Agency for Research on Cancer (IARC) as definitely carcinogenic. However, given the complex nature of the chemicals, the phasing out of the use of certain chemicals, and the trend in reduction in exposures, there remains a great deal of uncertainty about the nature of the risks, if any, encountered by workers today. Method: We have at our disposal a large retrospective cohort study of 40 000+ workers who were aged 35+ in 1967, which was last followed up to 1976. We are carrying out an updated cancer mortality analysis adding 35 years to the previous cancer mortality follow-up. We will determine the nature of the dose-response relationships for important known and suspected carcinogens using quantitative exposure modelling based on available measurement data from the EXASRUB project (dust, fumes, solvents, and n-Nitrosamines). Results: We will report on progress to date with the study, which has received ethical approval and is currently seeking other clearances from the UK research governance system for such studies, and will further report on proposed exposure modelling strategies. Conclusions: This is the largest and statistically most powerful cohort of its type and will have an exhaustive, quantitative exposure assessment. This study will add substantially to our knowledge of the longterm risks associated with the chemicals present in the industry in the UK, including those from working conditions several decades ago, and will thereby also be important for exposure conditions in the developing world.